Contributions of Increasing Obesity and Diabetes to Slowing Decline in Subclinical Coronary Artery Disease. Issue 4 (22nd April 2015) - Smith, Carin Y.; Bailey, Kent R.; Emerson, Jane A.; Nemetz, Peter N.; Roger, Véronique L.; Palumbo, Pasquale J.; Edwards, William D.; Leibson, Cynthia L.
Abstract : Background: Our previous study of nonelderly adult decedents with nonnatural (accident, suicide, or homicide) cause of death (96% autopsy rate) between 1981 and 2004 revealed that the decline in subclinical coronary artery disease (CAD) ended in the mid‐1990s. The present study investigated the contributions of trends in obesity and diabetes mellitus to patterns of subclinical CAD and explored whether the end of the decline in CAD persisted. Methods and Results: We reviewed provider‐linked medical records for all residents of Olmsted County, Minnesota, who died from nonnatural causes within the age range of 16 to 64 years between 1981 and 2009 and who had CAD graded at autopsy. We estimated trends in CAD risk factors including age, sex, systolic blood pressure, diabetes (qualifying fasting glucose or medication), body mass index, smoking, and diagnosed hyperlipidemia. Using multiple regression, we tested for significant associations between trends in CAD risk factors and CAD grade and assessed the contribution of trends in diabetes and obesity to CAD trends. The 545 autopsied decedents with recorded CAD grade exhibited significant declines between 1981 and 2009 in systolic blood pressure and smoking and significant increases in blood pressure medication, diabetes, and body mass index ≥30 kg/m 2 . An overall decline in CAD grade between 1981 and 2009 was nonlinear and ended in 1994. Trends in obesity and diabetes contributed to the end of CAD decline. Conclusions: Despite continued reductions in smoking and blood pressure values, the previously observed end to the decline in subclinical CAD among nonelderly adult decedents was apparent through 2009, corresponding with increasing obesity and diabetes in that population.